Behavior Coding of Adolescent and Therapy Dog Interactions During a Social Stress Task - Seana Dowling-Guyer; Katie Dabney; Elizabeth A. R. Robertson; Megan K. Mueller (Veterinary Sciences)
Youth mental health interventions incorporating trained therapy animals are increasingly popular, but more research is needed to understand the specific interactive behaviors between participants and therapy dogs. Understanding the role of these interactive behaviors is important for supporting both intervention efficacy and animal welfare and well-being. The goal of this study was to develop ethograms to assess interactive behaviors (including both affiliative and stress-related behaviors) of participants and therapy dogs during a social stress task, explore the relationship between human and dog behaviors, and assess how these behaviors may vary between experimental conditions with varying levels of physical contact with the therapy dog. Using video data from a previous experimental study (n = 50 human–therapy dog interactions, n = 25 control group), we successfully developed behavioral ethograms that could be used with a high degree of interrater reliability. Results indicated differences between experimental conditions in dog and human behaviors based on whether participants were interacting with a live or a stuffed dog, and whether they were allowed to touch the dog. These findings suggest that physically interacting with a live dog may be an important feature of these interventions, with participants demonstrating increased positive behaviors such as laughing and smiling in these conditions. Dog behaviors also varied based on whether they were in the touching/petting condition of the study which could indicate reactions to the session and has potential welfare implications for the dogs. Future research should focus on identifying specific patterns of interactive behaviors between dogs and humans that predict anxiolytic outcomes.